Application of Analytical Network Process and Conditional Probability Co-occurrences Matrix for Business Modelling of Small-Medium Enterprises - Mirwan Ushada; Henry Yuliando (Agroindustrial Journal, 2017)
In Indonesia, the scope of agroindustry are related to the food and non-food industry managedby Small-Medium Enterprises (SME). The classical problem of Indonesian Agroindustry wererelated to logistic, infrastructure, technology, high-cost economy, regulation, and financingconstraint. Therefore, an innovative business model is required for competitive and sustainableSME. Importance rate of the model can be defined by determining some criteria in a businessmodel. Analytical Network Process (ANP) is required to determine importance rate of businessmodel. However, ANP could not minimize the subjectivity factor of the respondent indetermining the criteria. Application of Conditional Probability Co-occurrences Matrix (CPCM)is required to minimize the subjectivity factor by comparing priority weight of each criterias. Theresearch objectives are: 1) To apply ANP method for representing business model criteria andattribute of SME; 2) To apply CPCM method for criteria pattern extraction. The case study ofresearch is SME Bakpia Tela Ungu and Telopia. CPCM Pattern extraction of Contrast, Energyand Local Homogeneity indicated the significant different of business model criteria betweenfood, non-food agroindustry and local governmental board. The research results indicated thatthere were different subjectivity to determine criteria priority weight.